A spatially-structured PCG method for content diversity in a Physics-based simulation game - Lara-Cabrera, Raúl; Gutiérrez-Alcoba, Alejandro; Fernández-Leiva, Antonio José (My University, 2016)
This paper presents a spatially-structured evolutionary algorithm (EA) to procedurally generate game maps of di ferent levels of di ficulty to be solved, in Gravityvolve!, a physics-based simulation videogame that we have implemented and which is inspired by the n- body problem, a classical problem in the fi eld of physics and mathematics. The proposal consists of a steady-state EA whose population is partitioned into three groups according to the di ficulty of the generated content (hard, medium or easy) which can be easily adapted to handle the automatic creation of content of diverse nature in other games. In addition, we present three fitness functions, based on multiple criteria (i.e:, intersections, gravitational acceleration and simulations), that were used experimentally to conduct the search process for creating a database of maps with di ferent di ficulty in Gravityvolve!.
Keywords: Computación evolutiva; Procedural content generation; Games; Evolutionary computation; Artificial Intelligence